The Accumulation Of Chloroplast Small Rnas In Chlamydomonas Reinhardtii During Nitrogen Deprivation - Che Ani, Mohd Suhaimi (2022)
The effects of the availability of nitrogen to chloroplast bioenergetics are beneficial and very significant that need to be explored. Small RNAs have been identified from the genome of chloroplasts, yet limited information exists on the response of small RNAs to chloroplasts during nitrogen deprivation. In this study, the participation of small RNAs is explored in order to gain a better understanding of their roles in algae's regulatory mechanisms during stress adaptation. A comparative transcriptomic survey was conducted to find chloroplast small RNAs that respond to nitrogen deprivation in the microalgae Chlamydomonas reinhardtii. Growth in nitrogen-deprived medium revealed 22 significantly over-accumulated and 18 lessaccumulated chloroplast small RNAs. The genomic locations of these small RNAs varied covering regions that were either untranslated, or coded in the sense or antisense direction, or the ends of the tRNA and rRNA genes.